ANALISIS KEUNTUNGAN USAHA INDUSTRI RUMAH TANGGA KOPI ROBUSTA BUBUK BIJI MERAH DI DESA LIBERIA TIMUR KECAMATAN MODAYAG KABUPATEN BOLAANG MONGONDOW TIMUR (Business Profit Analysis Of Household Industry Of Robusta Coffee Red Seed Powder In East Liberia Village, Modayag Sub District, East Bolaang Mongondow Regency) - Vieky Mirah; Audrey J. M. Maweikere; Olfie L. S. Benu (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2022)
The objective of this study is to calculate and analyze the profits of the home industry of Mr. Hamid's Robusta coffee, red bean powder. The data used in May 2021. The analysis of the data used in this study is an analysis of the profits of the home industry of